APPLICATION OF CLAIMS FOR PAYMENT IN HOUSE USING ATE SEAFOOD LARASATIMU VISUAL FOXPRO 9.0 - Fencing Prasetyo; Ire Puspa Wardhani, SKom, MM (Jurnal Sistem Informasi, 2009)
Billing Application Payments On Larasatimu Seafood Restaurant is designed to facilitate the carrying out payments so that payments become more effective and efficient.            Claims for Payment Applications built using Microsoft Visual FoxPro 9.0 for using Microsoft Visual FoxPro 9.0 applications is made easy bill payments designed to utilize the various facilities provided by Microsoft Visual FoxPro 9.0, so it  is easy to use application.